Fundamental Of Entrepreneurship (ENT300) Business Model Canvas (BMC) : Bibimbap Kitchen / Nurul Syahirah Akmal Aziz - Akmal Aziz, Nurul Syahirah (2020)
Korean cuisine is the customary cooking traditions and practices of the culinary arts of Korea. Korean cuisine has evolved through centuries of social and political change. Originating from ancient agricultural and nomadic traditions in Korea and southern Manchuria, Korean cuisine has evolved through a complex interaction of the natural environment and different cultural trends.